Bioelectricity (electromicrobiology) and sustainability. Issue 5 (14th August 2017) - Nealson, Kenneth H.
Summary: Electromicrobiology is the domain of those prokaryotes able to interact with charged electrodes, using them as electron donors and/or electron acceptors. This is performed via a process called extracellular electron transport, in which outer membrane cytochromes are used to oxidize and/or reduce otherwise unavailable insoluble electron acceptors. EET‐capable bacteria can thus be used for a variety of purposes, ranging from small power sources, water reclamation, to pollution remediation and electrosynthesis. Because the study of EET‐capable bacteria is in its nascent phase, the applications are mostly in developmental stages, but the potential for significant contributions to environmental quality is high and moving forward. Abstract :